2006
DOI: 10.1590/s0103-84782006000500016
|View full text |Cite
|
Sign up to set email alerts
|

Estado neurológico e cardiorrespiratório de filhotes de cães nascidos de parto normal ou de cesariana sob anestesia geral inalatória com sevofluorano

Abstract: RESUMO A anestesia obstétrica possibilita um procedimento mais seguro para a mãe e para os fetos. Em medicina veterinária, no entanto, a literatura científica a respeito do assunto é deficiente. Este trabalho teve como objetivo avaliar INTRODUÇÃOEm medicina veterinária, nota-se a necessidade de maiores estudos referentes aos procedimentos anestésicos em gestantes, pois as informações a respeito da anestesia nesses pacientes e de seus efeitos nos fetos são escassas. Devido às propriedades físico-químicas dos fá… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 5 publications
2
6
0
2
Order By: Relevance
“…Blood gas analyses performed on venous blood samples from the umbilical cord (Table 3) showed high PCO 2 values coupled with low pH, which suggests a scenario of respiratory acidosis and severe acidemia at birth. These results corroborate other findings of low pH and high PCO 2 of puppies born by cesarean surgery in three studies (Crissiuma et al 2006, Gabas et al 2006, Lucio et al 2009. This scenario is also commonly observed during natural labor, as demonstrated by one study using umbilical cord blood samples (Vivan et al 2009) that found high PCO 2 values (65±32mmHg) and low pH (7.1±0.2).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Blood gas analyses performed on venous blood samples from the umbilical cord (Table 3) showed high PCO 2 values coupled with low pH, which suggests a scenario of respiratory acidosis and severe acidemia at birth. These results corroborate other findings of low pH and high PCO 2 of puppies born by cesarean surgery in three studies (Crissiuma et al 2006, Gabas et al 2006, Lucio et al 2009. This scenario is also commonly observed during natural labor, as demonstrated by one study using umbilical cord blood samples (Vivan et al 2009) that found high PCO 2 values (65±32mmHg) and low pH (7.1±0.2).…”
Section: Discussionsupporting
confidence: 91%
“…Neonatal respiratory depression is aggravated by general anesthesia during cesarean surgery owing to the effects of the anesthetics together with the recumbent position of the mother, which causes a decrease in arterial blood pressure and uterine blood flow. These effects indirectly affect fetal viability by decreasing transplacental oxygen transfer in conjunction with the direct depression of the fetuses by the anesthetics (Gabas et al 2006, Lucio et al 2009.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In veterinary medicine, there are no studies that consolidate the Apgar score for different species. Some adaptations support the measurement of heart rate (HR), respiratory activity, muscle tone, colour of mucous membranes and vocalization (Moon et al 2001;Gabas et al 2006).…”
Section: Introductionmentioning
confidence: 99%